2011
DOI: 10.1364/oe.19.014801
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic imaging method based on arc-direction compressed sensing and multi-angle observation

Abstract: In photoacoustic imaging (PAI), the photoacoustic (PA) signal can be observed only from limit-view angles due to some structure limitations. As a result, data incompleteness artifacts appear and some image details lose. An arc-direction mask in PA data acquisition and arc-direction compressed sensing (CS) reconstruction algorithm are proposed instead of the conventional rectangle CS methods for PAI. The proposed method can effectively realize the compression of the PA data along the arc line and exactly recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Fortunately, most medical images are sparse in a certain domain by finding an appropriate sparse transform : = ψ x ψθ , where θ is the original image, and x is the transformed one. It has been proven that photoacoustic images can be transformed into sparse domains by a variety of transforms, such as the numerical derivative (ND), the wavelet transform, etc [16][17][18][19].…”
Section: Compressed Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, most medical images are sparse in a certain domain by finding an appropriate sparse transform : = ψ x ψθ , where θ is the original image, and x is the transformed one. It has been proven that photoacoustic images can be transformed into sparse domains by a variety of transforms, such as the numerical derivative (ND), the wavelet transform, etc [16][17][18][19].…”
Section: Compressed Sensingmentioning
confidence: 99%
“…Recently, explorations aiming to leverage the advantages of CS for PACT have also been reported. For example, J. Provost et al have conducted numerical and phantom studies on CS-based PACT [16]; D. Liang et al have numerically demonstrated CS-based photoacoustic imaging under random optical illumination [17]; Z. Guo et al have reported CS-based photoacoustic reconstruction in time domain with images acquired in vivo [18]; M. Sun et al have developed an arc-direction compressed-sensing PACT algorithm with numerical phantoms [19]. All these studies have shown that CS-based reconstruction techniques can recover photoacoustic signals sampled at a (temporal and/or spatial) rate lower than that required by the Nyquist sampling theory.…”
Section: Introductionmentioning
confidence: 99%
“…(3) is based on the common assumption that the reconstructed image may be sparsely represented in an alternative basis. [24][25][26][27][28][29] To perform the inversion, the following procedure is applied. First, the image to be recovered u is transferred into a basis in which it is expected to be sparse: x = Φu, where x is the representation of u in the new domain and Φ is the transform matrix.…”
Section: A1 L1 Regularizationmentioning
confidence: 99%
“…More recent regularization approaches are based on either penalizing the total variation (TV) of the image [20][21][22][23] or enforcing sparsity on its representation in an alternative basis, e.g., a wavelet basis. [24][25][26][27][28][29] Both of these regularization approaches have been shown to produce sharper, cleaner images than energy-minimization regularization in several imaging scenario, and their combination has been used in image denoising. 30 Nonetheless, demonstration on experimental data has been limited to only tissue-mimicking phantoms 29 or experiments in mice that focused on imaging vascularization.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of artifacts and loss of resolution in limited-view imaging can be addressed by using random optical illuminations for fast data acquisition via the SPGL1 algorithm [15, 16]. Sun et al have developed an arc-direction compressed-sensing PAT algorithm with numerical phantoms [17]. Both phantom and in vivo results showed that the CS method can effectively reduce undersampling artifacts via the nonlinear conjugate gradient descent algorithm [18, 19].…”
Section: Introductionmentioning
confidence: 99%